2023
DOI: 10.7812/tpp/23.018
|View full text |Cite
|
Sign up to set email alerts
|

Art Interventions to Mitigate Burnout in Health Care Professionals: A Systematic Review

Abstract: Burnout in the medical workforce is a growing global concern. Visual arts–based interventions can be a novel way to mitigate burnout and bolster resilience in medicine. Improving tolerance of ambiguity and uncertainty has been associated with decreased rates of burnout in clinicians. No known systematic review exists summarizing the evidence behind the use of visual arts–based interventions to mitigate burnout in clinicians. The authors conducted a systematic literature review of PubMed, EMBASE, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In 2023, Engel et al reviewed these interventions based on art therapy and showed that empathy, connection, and tolerance of ambiguity could be promoted and that this can positively affect burnout [13].…”
Section: Introductionmentioning
confidence: 99%
“…In 2023, Engel et al reviewed these interventions based on art therapy and showed that empathy, connection, and tolerance of ambiguity could be promoted and that this can positively affect burnout [13].…”
Section: Introductionmentioning
confidence: 99%